Incidence, clinical and genomic trends of hospital- and Non-hospital-onset KPC-producing Klebsiella pneumoniae infections before and during the COVID-19 era: a ten-year interrupted time series study - Manuel Recio-Rufián; Teresa López-Viñau; Víctor Gálvez-Soto; Ángela Cano; Rafael Ruiz-Montero; Belén Gutiérrez-Gutiérrez; Irene Gracia-Ahufinger; Germán Peñalva; Juan Antonio Marín-Sanz; Miriam Marín-Sanz; David Segorbe; Juan Jesús Pineda-Capitán; et al. (Antimicrobial Resistance and Infection Control)
Abstract Background Infections caused by KPC-producing Klebsiella pneumoniae (KPC-KP) represent a persistent public health challenge. This prospective study examines ten-year trends, clinical features, and genomic epidemiology of hospital-onset (HOI) and non-hospital-onset (non-HOI, including healthcare-associated [HcAI] and community-acquired [CA]) KPC-KP infections following a 2012 outbreak. We evaluated the impacts of a 2014 antimicrobial stewardship program (ASP) and COVID-19-related infection prevention and control (IPC) measures, with emphasis on hospital-to-community dissemination. Methods We analysed a prospective, longitudinal cohort of patients (2012–2022) in a tertiary referral hospital. Interrupted time series and ARIMA models assessed ASP and IPC impacts on incidence density (ID). Cross-correlation analysis explored temporal associations between HOI and non-HOI trends. Whole-genome sequencing and PERMANOVA evaluated the genomic structure of ST512/KPC-3 isolates. Multivariable regression analysed the association between infection type and clinical outcomes. Results Among 467 patients, 33.2% had non-HOI (ID 0.53/1,000 admissions/month) and 66.8% HOI (ID 0.30, p = 0.39). Urinary tract infections predominated in non-HOI (52.9%), while bloodstream and respiratory infections were more common in HOI. Incidence density of HOI and non-HOI infections declined significantly following ASP implementation, with a 4-month lag suggesting sequential transmission dynamics. These reductions were maintained during the pandemic. Genomic data confirmed ST512/KPC-3 dominance and hospital-to-community spread, with temporal factors—rather than acquisition type—explaining genetic variation. Adjusted analyses showed similar 30-day mortality and treatment responses across HOI and non-HOI. Conclusions ASP and COVID-19 IPC measures contributed to maintaining low KPC-KP incidence. Genomic evidence underscores the role of temporal dynamics and clonal expansion in ST512/KPC-3 dissemination. Non-HOI infections are clinically significant and require targeted, system-wide surveillance and control strategies.